Kualitas Hidup dalam Perspektif Ajaran Qur'an - Burhanuddin Ridlwan (Menara Tebuireng, 2018)
Quality of life has a lot of understanding, and the amount of understanding is determined by the position of life subjectivity in the context of culture and value systems, which relate to life goals, expectations, standards, and focus in life where the individual is. So that the quality of life is not just meant to be safe in terms of financial or health, but has a wider scope. Some experts give the understanding that quality of life is a person's perception of life welfare that comes from satisfaction and dissatisfaction with what is lived in life, quality of life is influenced by many experiences and then evaluated with positive or negative feelings by individuals, and quality of life is the reality experienced by the individual is compared to the intended goal. Then the quality of life includes evaluating individuals who are subjective, who are embedded in the cultural, social, and environmental context. Therefore the quality of life cannot be equated with health status, lifestyle, social and economic status, as well as the level of welfare and satisfaction. However, the quality of life depends on a value system that focuses on individual perceptions in the context of culture, culture, social, political, spiritual or religious and belief. The research method used in this study is the study of literature (Library Research) or literary studies, namely a study carried out to solve a problem that relies on a critical and in-depth review of relevant library materials in accordance with the focus of the research. While the focus of the research is: (1) The essence of the understanding of quality of life, the nature of understanding of the quran, and how to understand the quality of life in the perspective of quran teachings. The results of this study are, first: the essence of the definition of quality of life is the individual's perception of their position in life in the context of the culture and value system in which they live, in relation to their life goals, hopes, standards and focus, with a view that quality includes subjective evaluations of individuals embedded in cultural, social and environmental contexts, hence the quality of life cannot be equated only with terms of health status, lifestyle, satisfaction, mental condition and well-being. The quality of life in Islam is determined by: quality of work and pious charity, quality of faith and piety, quality of knowledge or intellectual, and social quality. Second: the essence of understanding quran is kalamullah megandung mu'jizat, which is revealed to the prophet Muhammad s.a.w. through the angel Gabriel, which is written in the Mushkhaf, which is narrated by means of mutawatir, and which is worth worshiping for those who read it. Third: quality of life in the perspective of the Qur'anic teachings is divided into four areas that determine quality of life, namely: relating to the principle or teaching that quality of life is determined by the quality of works and pious deeds, determined by the quality of faith and piety, determined by the quality of knowledge or intellectual quality, and determined by social quality